Exploring the role of the Chief Information Officier (CIO) during a failing IS initiative : a process inquiry in a public sector setting - Dempsey, Brian (Trinity College (Dublin, Ireland). Trinity Business School, 2015)
This research is situated in the field of Information Systems (IS) and explores the role of the Chief Information Officer (CIO) over the course of a failing IS initiative. IS failure is a recurring theme in both academic and practitioner literature since the beginning of the computer age. Studies of IS failure indicate that it is widespread and is costing industry in the tens of billions of US$ per annum. The Chief Information Officer (CIO) is described as a senior executive with responsibility for establishing corporate information policy, standards, and management control of all corporate information resources.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin